COMPARATIVE CHARACTERISTICS OF THE MOTOR POTENTIAL OF CHILDREN 7-10 YEARS OLD WITH THE REGULATIVE REQUIREMENTS OF THE FIRST AND SECOND AGE GROUPS OF THE “SALOMATLIK” HEALTH TESTS - Tillaev Sharifjon Omonboevich (Journals Park Publishing, 2023)
The article studies the issues of adequate comparability of normative indicators of motor fitness of children of primary school age with the requirements of health tests " Salomatlik "
Keywords: Motor fitness, primary school age, sensitive age period, heterochrony , normative indicators, Salomatlik health tests.